Sistem Penyiraman Tanaman Otomatis Berbasis IoT Menggunakan ESP32, Moisture Sensor, DHT22 Sensor dan Blynk - Dwianti Westari; Syaeful Ilman (Pusat Riset dan Inovasi Nasional, 2024)
The Internet of Things (IoT) technology has brought innovation to various fields, including agriculture and plantations. One of the main challenges in plant cultivation is maintaining consistent irrigation to ensure that plants receive an optimal amount of water. Improper watering can lead to either water deficiency or excess, negatively impacting plant growth and productivity. An IoT-based automatic irrigation system is designed to address this issue by utilizing soil moisture, temperature, and humidity sensors to accurately determine the water needs of plants. The data collected by the sensors is processed by a microcontroller, which then automatically controls the water pump. Additionally, users can monitor and manage irrigation through a smartphone application, allowing for more efficient and flexible watering. With the implementation of this system, it is expected that productivity and efficiency in plant management, both at the household and commercial farming levels, can be significantly improved.